Comparison of performance for winning and losing beach volleyball teams on different court dimensions. - Giatsis, G.; Tzetzis, G. (International Journal of Performance Analysis in Sport, 2003)
The purpose of this study was to investigate and compare the performance between winning and losing teams in Beach Volleyball (BV) matches on courts of new (8x8m) and old dimensions (9x9m) at the side out phase. Side out in BV means the change of the right to serve Nine semifinals and seven finals of the Hellenic BV Championship taking place at an 8x8m and 9x9m court were video-recorded using a camera. 34 sets and 1466 phases were recorded and the following technical skills were analyzed: a) serve b) reception c) attack. In addition, attack was divided into two categories according to the type of the attack: a) spikes and b) shots. The term effectiveness was established by the ratio determining the total kills minus total errors divided by total attempts. Independent samples t-test was used in order to compare the above mentioned parameters between the winning (N) and losing (H) teams at these two different court dimensions (8x8, 9x9). Significant differences were found, t(16) = 3.06, p< .01), in the attack efficiency (MN8x8 = .476, SD = .086, MH8x8 = .315, SD = .131), (t(18) = 2.44, p< .05), in the spike efficiency (MN8x8 = .479, SD = .162, MH8x8 = .254, SD = .236), in the percentage of errors (MN8x8 = .139, SD = .052, MH8x8 = .204, SD = .077), (t(18) = 2.21, p< .05), in the percentage of receptions errors (MN9x9 = .09, SD = .043, MH9x9= .032, SD = .029), t(10) = 2.73, p< .05) and in reception (MH9x9 = 0.96, SD = 0.03, MH9x9 = 0.90, SD = 0.05), (t(10) = 2.74, p< 0.05). Winning and losing teams used the spikes and shots at approximately the same rate. In conclusion, different skills performance contributed to winning the match after the reduction in court dimensions. On the 8x8, the winners had better attack efficiency and fewer errors, while on the 9x9 they had better reception.